Risk of secondary autoimmune diseases with alemtuzumab treatment for multiple sclerosis: a systematic review and meta-analysis - Yang, Jianguo; Sun, Yuying; Zhou, Xinpeng; Zhang, Di; Xu, Ziqi; Cao, Jiaojiao; Fan, Bing (Frontiers in Immunology, 2024)
Background and purpose: The objective of this study is to evaluate the risk of secondary autoimmune diseases in multiple sclerosis (MS) patients treated with alemtuzumab (ALZ) through a meta-analysis. Methods: PubMed, Web of Science, OVID, EMBASE, and Cochrane central register of controlled trials were searched. Information and data were screened and extracted by 2 researchers. The obtained data were analyzed using the R software meta package. Quality assessment was conducted using the Newcastle-Ottawa Scale (NOS). The causes of heterogeneity were analyzed using subgroup analysis and sensitivity analysis. Publication bias was evaluated using funnel plots and Egger’s test. Results: The search retrieved a total of 3530 papers from the databases. After screening, a total of 37 studies were included in the meta-analysis. The analysis results indicate that the pooled incidence rate of overall secondary autoimmune events (SAEs) in the included studies was 0.2824 [0.2348, 0.3300] (I²=94%, p<0.01). The overall incidence of autoimmune thyroid events (ATE) was 0.2257 [0.1810, 0.2703] (I²=94%, p<0.01). Among them, the rate of serious autoimmune thyroid events (SATE) was 0.0541 [0.0396, 0.0687] (I²=0%, p=0.44). The incidence rates of different thyroid events were as follows: Graves' disease (GD), Hashimoto thyroiditis (HT), Hashimoto thyroiditis with hypothyroidism (HTwH), fluctuating thyroid dysfunction (FTD), transient thyroiditis (TT). The overall incidence of hematological events was 0.0431 [0.0274, 0.0621] (I²=70%, p<0.01). The incidence rates from high to low were as follows: lymphopenia, Idiopathic thrombocytopenic purpura (ITP), Hemolytic anemia (HA), pancytopenia, Neutropenia. After excluding thyroid and hematological diseases, the combined incidence of other related SAEs was 0.0061 [0.0014, 0.0109] (I²=50%, p=0.02). The incidence of each disease ranked from highest to lowest as: skin psoriasis (SP), alopecia areata (AA), vitiligo, inflammatory atrichia (IA), chronic urticaria (CU), and nephropathy. Conclusion: The occurrence of secondary autoimmune diseases in patients with MS treated with ALZ is noteworthy, particularly in the form of thyroid events and hematological events. Clinicians should monitor the overall condition of patients promptly for early management and avoid delayed diagnosis and treatment.